Analisis Faktor-Faktor yang Mempengaruhi Harga Saham pada Perusahaan Perbankan yag Terdaftar di Bursa Efek Indonesia - Jessyana; Dian Efriyenti (SCIENTIA JOURNAL, 2022)
To approve the effect of Profitability, Liquidity, and Solvency to Stock Price in banking companies and has been listed on the IDX. ROA, LDR, dan DAR as independent variables and Stock Price as dependen. tvariable to periode 2016-2020. This study used a purposive sampling sample with data collection techniques using documentation techniques. 39 companies that meet these criteria. The testing in the form of classical assumptions, multiple linear regression and hypothesis testing using SPSS. The result show that ROA has a positive effect on stock price with tcount > ttable that is 5,912 > 1,992 with significant level is 0,000 < 0,05, LDR has a positive effect not significant on stock price with tcount > ttable that is 406 < 1,992 with significant level of 0,685 < 0,05, DAR has a negative effect on stock price with tcount > ttable that is -3,803 > -1,992 and the significant level is 0,000 < 0,05. The result of F test show that ROA, LDR and DAR simultaneously influence to stock price with Fcount > Ftable that is 14,762 > 2,65 and the significant level is 0,000 < 0,05.. Keywords: Debt to Assets Ratio; Loan to Deposit Ratio; Return on Assets; Stock Price.